Timosin alpha-1 immunomodulating properties - M. V. Mayevskaya (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To present modern data on the mechanism of action and clinical utilization of immunomodulating agent «Timosin alpha-1».Original positions of the report. Timosin alpha1 is 28-base acetylated polypeptide, that effectively modulates human immune system and has direct action on the cells infected by virus that allows to talk of its «double» mechanism of action. Immunomodulating effect of Timosin alpha-1 consists in increase of natural killer cells number, CD4 and CD8 by stimulation of stem cells differentiation and decrease of T-cells apoptosis, and also in driving of immune response to Th1 subtype by increase of Th1 cytokines (IL-2, IFN) amount and decreases of amount of Th2 cytokines (IL-4, IL-10). Direct antiviral mechanism of Timosin alpha-1 consists in increase of expression of major histocompatibility complex molecules of the 1st class on infected cells and direct suppression of virus replication, and also in elevation of endocellular level of glutathione. Combination of Timosin alpha-1 and interferon-a (IFN-a) induces substantial increase of IL-2 level and blocks elevation of IL-10 level invoked by IFN-a that can be successfully utilized in chronic hepatitis B (CHB) treatment. Results of metaanalysis of 4 randomized controlled studies in which efficacy of Timosin alpha-1 and IFNб was compared in treatment of CHB (total number of patients – 199) were published. It is shown, that Timosin alpha-1 efficacy is increased eventually and is more pronounced at the end of monitoring period after termination of therapy. According to original studies The Asian-Pacific association for the study of the liver (APASL) included Timosin alpha-1 in the list of immunomodulating agents for CHB treatment besides standard and pegilated interferon-a (PEG-IFN-a). Efficacy of Timosin alpha-1 was demonstrated in the treatment of one of the most difficult groups of patients with persistent hepatitis C virus infection – non-responders at combined treatment by interferon and ribavirin. Timosin alpha-1 can be applied at immune antineoplastic therapy, in particular in treatment of hepatocellular carcinoma which is related to a final stage of persistent infection of hepatitis B and C viruses, that, as a rule, develops on a background of liver cirrhosis and in Caucasian patients.Conclusion. Timosin alpha-1 is successfully applied in clinical practice in treatment of chronic viral hepatites B and C, as antineoplastic immunomodulating drug and requires further active studies.